Type of Benefits Factors in The Implementation of Green Space Policy in Bandung City - Fidowaty, Tatik; Redjo, Samugyo Ibnu (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was to determine the type of benefits factor in implementing the Green Space policy in Bandung City. This study uses a descriptive research method with a qualitative approach. Data collection techniques used are literature study, observation, interviews with the Mayor of Bandung, the Bandung City Spatial Planning Service, the Department of Housing and Settlements, Land and Landscaping (DPKP3) Bandung City and the people of Bandung City. The technique of determining informants using purposive for government officials and accidental for the people of Bandung City. The results showed that Green Space has many benefits, including as a place for recreation and beauty. People visit the city forest of BabakanSiliwangi to breathe fresh air while exercising, want to see the green plants, relax while chatting. The point is you want to release your fatigue from your daily activities. Based on the explanation above, it can be concluded that the type of benefits factor can already be felt by various parties, although it is not evenly distributed because indeed the benefits of this Green Space are so many. Each party feels the benefits of Green Space from different perspectives or needs. If there are parties who feel aggrieved in the management of Green Spaces, the road will eventually be resolved in court.